Análise da contribuição do planejamento por cenários no gerenciamento do risco de estratégia dos bancos no Brasil: um estudo de caso - Tacini, Adalberto (2015)
The increased complexity in the economic and financial environment all over the world rose the uncertainty level for financial institutions and the National Financial System (SFN). In this context, the Central Bank (Banco Central do Brasil - BCB), responsible for authorizing, regulating and intervening in the banking market, along with other countries, requires that banks in Brazil prepare a management Strategy Risk within the capital managing process. This work aims to analyze the contribution of a management strategy technique, scenario planning, in the management of the risks. It is a relevant study because of bank strategic role in the economy and the importance of strategy management risks for SFN. This research has a qualitative and exploratory nature, uses case study methodology and aims the comprehension of an organizational phenomenal. It is supported by Administrational Paradigms and by Gareth Morgan s model. It also utilizes a historical analysis on the SFN and the Brazilian Banking Market. As a result, we observe that planning for scenarios, among other forms, contributes with the risk management strategy as (i) makes the decision-making process more qualified by considering different futures alternatives, (ii) makes the perception of risk inherent in decisions made clearer when organizing and delimit the uncertainties of the business environment and (iii) benefits to senior management by anticipation of possible significant variations in the business environment